Da carta pessoal ao e-mail: uma proposta de retextualização para o ano final do segundo segmento da Educação de Jovens e Adultos - Araújo, Lenilúcia Bilhar (2021)
Our current society is inserted in a context that reflects the importance of the use of digital media in interaction practices. Considering this assumption, it is the school's role to assume the part of mediator in this interaction endorsing students' access to the universe of texts that circulate socially in the virtual sphere, teaching them to interpret and produce them. To accomplish that, this paper aims to develop the reading and writing skills through the process of retextualization of personal letters, considering their compositional structure and the interactive use required by both genres, by final year students of the second segment of Youth and Adult Education – EJA. This paper is an attempt to find and analyze the need of EJA students regarding the lack of access to digital media and, at the same time, to provide them with a form of functional learning in the use of e-mails, aiming to contribute fulfill a contemporary social practice, also envisioning professional practice. For the apprehension of the letter and e-mail genres, mediated by retextualization, activities based on the didactic sequence of Dolz, Noverraz and Schneuwly (2004) were applied, which appear in the form of a Didactic Book to help the EJA teacher who needs to appropriate a teaching /learning oriented by the guidelines of the PCN (1998) and BNCC (2017). It is worth mentioning that the present proposal uses the summary as a didactic resource in the work with retextualization. This theoretical context is supported by Moreira (2008) and Machado’s (2010) research; on gender, the theoretical contribution comes from Bakhtin (1992, 1997, 2003, 2016) and Bronckart (1999, 2008); regarding the personal letter, there is the support of Pessoa (2002), Zanotto (2005), Menezes (2005). To address the email genre, the research focuses mainly on the studies of Todorov (1990), Marcuschi (2004; 2010), Coscarelli (2009). In order to deal with retextualization, we use the conceptions of Marcuschi (2001; 2010). Then, we are inspired by the ideas of Dell'Isola (2007), which focused on the retextualization in a didactic way, in the classroom. Another important contribution comes from Matencio (2003) and Dikson (2019). Through this paper, we look forward that significant outcomes will be achieved, especially in the development of students' reading and written production skills, acting on the improvement of textual competence, particularly in the transformative capacity that, according to Charrolles (1979) through Travaglia (1997) and reproduced by Moreira (2008), it resembles from the ability to transform a text into another, focusing to what is necessary to keep it original and avoiding what is superfluous and can be eliminated without prejudice to the original text, maintaining the same meaning in the final text. Thus, the experience with retextualization allows to favor a strategy of productive use in the practice of interaction through texts, including considering the ability to summarize.